Partially amorphous nickel–iron layered double hydroxide nanosheet arrays for robust bifunctional electrocatalysis - Xie, Junfeng; Qu, Haichao; Lei, Fengcai; Peng, Xu; Liu, Weiwei; Gao, Li; Hao, Pin; Cui, Guanwei; Tang, Bo (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Bifunctional electrocatalysts that can boost energy-related reactions are urgently in demand for pursual of dual and even multiple targets towards practical applications such as energy conversion, clean fuel production and pollution treatment. Herein, we highlight that an in situ grown nickel–iron layered double hydroxide (NiFe LDH) nanosheet array catalyst with partially amorphous characteristics, rich native Ni 3+ ions and an optimal Ni : Fe ratio can exhibit robust performances on both the oxygen evolution reaction (OER) and the urea oxidation reaction (UOR). Benefitting from the partially amorphous feature, the catalytically active high-valence species are easy to generate and stabilize, thus further realizing enhanced electrooxidation activity with the aid of an internal 2D charge transfer pathway and native Ni 3+ ions. As expected, the partially amorphous catalyst exhibits a higher OER current of 284.4 mA cm −2 at an overpotential of 500 mV, which shows 2.2–10.0 times enhancement than the counterparts with various Ni : Fe ratios. In addition, the UOR current density of the partially amorphous catalyst at 1.8 V vs. RHE shows 1.6 and 2.4 times increment relative to fully amorphous and highly crystalline catalysts, and 2.7–9.4 fold larger than the catalysts with other Ni : Fe ratios. The optimization strategy of designing the partially amorphous bifunctional catalyst in this work may broaden the way of searching for advanced electrocatalysts for simultaneous waste water treatment and clean energy production.